2023
DOI: 10.1161/circheartfailure.122.010051
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Outcomes Associated With Interleukin-6 in Patients Recently Hospitalized for Heart Failure With Preserved Ejection Fraction

Abstract: Background: Inflammation may play a role in the pathophysiology of heart failure with preserved ejection fraction. We examined whether circulating levels of interleukin-6 identify patients at greater risk of adverse outcomes following hospitalization with heart failure with preserved ejection fraction. Methods: We assessed relationships between interleukin-6 (IL-6) tertiles (T1-3) and all-cause death, cardiovascular death, and subsequent heart failure h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…We found that vericiguat is able to change the intracellular cytokine composition in skeletal muscle cells and cardiomyocytes exposed to doxorubicin (Figure 5), inducing an anti-inflammatory phenotype. Myocardial and skeletal muscle cells with high levels of IL-1 and IL-6 are exposed to a greater risk of heart attack and rupture of myofibrils, respectively [69]. Recent clinical work associates high plasma levels of chemokine ligand 2 (CXCL2) with chronic heart failure and sarcopenia [70].…”
Section: Discussionmentioning
confidence: 99%
“…We found that vericiguat is able to change the intracellular cytokine composition in skeletal muscle cells and cardiomyocytes exposed to doxorubicin (Figure 5), inducing an anti-inflammatory phenotype. Myocardial and skeletal muscle cells with high levels of IL-1 and IL-6 are exposed to a greater risk of heart attack and rupture of myofibrils, respectively [69]. Recent clinical work associates high plasma levels of chemokine ligand 2 (CXCL2) with chronic heart failure and sarcopenia [70].…”
Section: Discussionmentioning
confidence: 99%
“…Both are associated with incident HFpEF in population studies and are highly prognostic in patients hospitalized for HFpEF. 6,7 GDF-15 promotes weight loss, modulates macrophage phenotypes, and may represent a homeostatic response to inflammation; GDF-15 inhibition is not yet an obvious approach for HF prevention. In contrast, a large clinical trial (ZEUS [A Research Study to Look at How Ziltivekimab Works Compared to Placebo in People With Cardiovascular Disease, Chronic Kidney Disease, and Inflammation]: NCT05021835) is testing whether the monoclonal IL-6 antibody ziltivekimab reduces cardiovascular events (including, as a secondary end point, HF hospitalizations) in patients with CKD.…”
Section: Incident Hfpef and Hfref In Patients With Ckdmentioning
confidence: 99%
“…16 In line with IL-1 blockade, IL-6 blockade (eg, with the monoclonal antibody tocilizumab) deserves to be evaluated because patients with HFpEF with high IL-6 were recently demonstrated to have both worse exercise hemodynamics and poor outcome. 17 Inhibition of myeloperoxidase which is abundantly present in neutrophile granulocytes, is also being evaluated. Preliminary findings are encouraging as a 3-month treatment period with the myeloperoxidase inhibitor AZD4831 downregulated expression of plasma biomarker pathways observed in poor outcome HFpEF.…”
Section: Anti-inflammatory and Antifibrotic Therapymentioning
confidence: 99%